Policy Implementation of Social Assistance Social Rehabilitation of Unfitable Houses in North Sulawesi Province by E-Government - Pangkerego, Jordan Oktavianus; Masengi, Evi E.; Wawointana, Thelma (JR Education, 2022)
The high need for housing that is not matched by financial capacity, especially for people living below the poverty line, actually creates several social problems, one of which is the proliferation of uninhabitable houses or commonly abbreviated as RTLH. The purpose of this study was to determine the implementation of the social rehabilitation assistance policy for uninhabitable houses in North Sulawesi province. The type of research used in this study is descriptive qualitative and the collection technique is by observation, interviews and documentation. The informants in this study were the Head of the Social Service, the Head of the Social Handling of the Poor, the general public (Publik) and the beneficiaries of the RS-RTLH assistance policy. In general, the results of this research are that the policy of Social Rehabilitation Assistance for Uninhabitable Houses in North Sulawesi Province is not running effectively, this can be seen based on the following findings: 1) Aspects of standard policies and objectives have supported the implementation of the RS - RTLH assistance policy in the Province North Sulawesi, which is regulated in North Sulawesi Governor Regulation Number 46 of 2017 concerning Regional Operations to Resolve Poverty through the Social Rehabilitation Program for Uninhabitable Houses in North Sulawesi Province , 2) In terms of the budget aspect, it does not support the implementation of hospital assistance policies - RTLH , 3) The Social Service lacks communication, socialization, counseling related to RS-RTLH assistance, and 4) The North Sulawesi Provincial Social Service is less effective in carrying out supervision starting from the planning stage, the implementation stage and the evaluation stage. The Social Service only relies on data recommended by the lurah/village head, as a result sometimes there is a polemic in the community that the provision of RS-RTLH assistance is considered not to be on target, there are still people who deserve assistance but do not receive assistance.